Development of folliculitis in a patient with recalcitrant pustular psoriasis following acitretin treatment: a case report / Nur Ashikin Ahmad, Tarita Taib and Meera Kuppusamy. - Ahmad, Nur Ashikin; Taib, Tarita; Kuppusamy, Meera (Universiti Teknologi MARA Cawangan Selangor, 2017)
Oral retinoids are among the drugs of choice for pustular psoriasis. Therapy with retinoids, including acitretin, is potent teratogens with other common side effects such as mucocutaneous involvement. Mucocutaneous side effects including dry lips (cheilitis), skin peeling, hair loss (alopecia), dry skin, or rhinitis are dose-related, with cheilitis occurring in more than 75% of patients receiving the highest doses of acitretin (75 mg/day). We report on a 37-year-old woman who developed folliculitis with acitretin which is a rare cutaneous side effect. She presented with eruptions pruritic papules with follicular pattern on anterior thigh and forearms after almost 1 year of treatment with acitretin (50mg OD) for pustular psoriasis. The skin lesion was treated successfully with skin dressing and antibiotic treatment and skin biopsy is suggestive of folliculitis. Several treatments for pustular psoriasis including topical steroids, methotrexate and oral prednisolone were ineffective or not tolerated. Treatment with acitretin which are 50mg OD provided partial resolution of skin lesions. The case is hereby reported because of its rarity and folliculitis must be considered in the differential diagnosis of a popular eruption, especially in patients with high dose acitretin.